2012
DOI: 10.1016/j.amjcard.2011.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Progression and Outcome of Asymptomatic Aortic Stenosis in Primary Care

Abstract: The prognostic relevance of a rapid rate of hemodynamic progression of aortic stenosis (AS) has been predominantly investigated in tertiary centers. We reviewed the clinical and echocardiographic data from 153 asymptomatic patients with AS (age 77 ± 9 years; 65% men), with normal left ventricular function and paired echocardiograms ≥4 months apart (mean 2.9 ± 2.1 years), evaluated in a nonreferral echocardiographic laboratory. The severity of AS was graded by the peak aortic velocity (Vmax) and progression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Nistri and colleagues demonstrated that the average increase in Vp was 0.26±0.32 m · s −1 · year −1 with great individual variability in hemodynamic progression. 30 The present study results were consistent with those reports. 2,30 There were few changes over time in LV geometry, mass, and systolic or diastolic function, which is also consistent with a previous study.…”
Section: Serial Tte Changes In Unoperated Patients With Asymptomatic Assupporting
confidence: 83%
“…Nistri and colleagues demonstrated that the average increase in Vp was 0.26±0.32 m · s −1 · year −1 with great individual variability in hemodynamic progression. 30 The present study results were consistent with those reports. 2,30 There were few changes over time in LV geometry, mass, and systolic or diastolic function, which is also consistent with a previous study.…”
Section: Serial Tte Changes In Unoperated Patients With Asymptomatic Assupporting
confidence: 83%
“…89-91 Although the current evidence-based guidelines recommend a watchful waiting approach for most asymptomatic patients, numerous studies have shown that patients with severe AS have a high likelihood of developing symptoms and requiring surgery within 3 to 5 years, 6,15,17,18 and other series have reported that asymptomatic patients with severe AS are also at risk of death when managed without surgery. 38,86 As the operative risk of AVR is low in experienced centers, 86,87 there is ongoing interest in identifying high risk asymptomatic patients who might benefit from early, preemptive AVR rather than a watchful waiting approach, as noted previously.…”
Section: Aortic Valve Replacementmentioning
confidence: 95%
“…6,17,18,38 Event-free survival of patients with V max >5 m/sec was 64%, 36%, and 25%, at 1, 2, and 3 years, respectively. 18 Patients with V max >5.5 m/sec developed more severe symptoms, with half presenting with NYHA class III or IV symptoms.…”
Section: Risk Stratification Of the Asymptomatic Patientmentioning
confidence: 98%
See 1 more Smart Citation
“…AS is a chronic and progressive disease, and rapid progression of AS is reported to be related to poor outcomes with asymptomatic AS. The progression rates of AS in previous studies11 32 4043 are shown in table 6. Although there have been many studies of mild-to-moderate AS,11 40–44 data describing the progression rate of severe AS are limited 32.…”
Section: Optimal Management Of Asymptomatic Severe As: Conventional Smentioning
confidence: 99%